Beyond Juvenile Delinquency: Youth Involvement as Perpetrators of Criminality - Fernando, Henky; Abdullah, Irwan; Larasati, Yuniar Galuh; Novarizal, Riky; Morin, Leanne (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2024)
Adolescents' involvement as perpetrators of criminality in Indonesia has gone beyond the patterns of deviant behavior and actions categorized as juvenile delinquency. Adolescents' involvement as perpetrators of criminality has not been given much scientific attention in previous studies. This study focuses on the question, "How is the involvement of adolescents as perpetrators of criminality that occurs in Indonesia?" This study uses a descriptive qualitative approach to exploring the forms, characteristics, and factors that influence a teenager to become a perpetrator of criminality disseminated through online media coverage. The collection and reading of online news focused on news titles containing criminality cases involving teenagers by using the search keyword "Involvement of teenagers as perpetrators of criminality in Indonesia" on the Google search engine. The findings in this study show that the involvement of teenagers as perpetrators of criminality has gone beyond the deviant behavior patterns of juvenile delinquency. The context can be reflected through the forms and characteristics of the acts committed by teenagers, ranging from maltreatment, drug abuse, to murder. This study also recommends the importance of looking at the welfare of adolescents as perpetrators of criminality and the law enforcement process to obtain a comprehensive and more empirical understanding.